Assessment of sheep wool waste as new resource for green building elements. (November 2022) - Parlato, Monica C.M.; Porto, Simona M.C.; Valenti, Francesca
Abstract: Within the context of circular economy framework and green deal statement, the valorization of greasy wool into new resources for insulation building components, represents an important challenge. The sustainable and innovative alternative uses of this livestock waste could create new opportunity for the growing of sheep farming sector and reduce environmental issues. By using Geographic Information Systems tools a tailored methodology has been carried out to evaluate the availability and geographical distribution of sheared sheep wool, with the aim of quantifying the correct scale required for a sustainable production of sheep wool insulation products. In detail, the hypothetical production of insualtion material based on wool waste, soft mats (100% wool) and semi-rigid panels (80% wool and 20% polyester), has been evalueted, at regional level and it was obtained that by reusing the computed sheep wool, i.e., 9, 839, 700 kg/year, more than 1, 5 millions of soft mats or more than 11, 5 millions of semi-rigid panels could be produced, which correspond, respectively, to more than 6.5 million and more than 17 thousand of square meter. These results, obtained by the conversion of raw wool into new resources, represent the first step for developing a new wool valorization chain. Graphical abstract: Image 1 Highlights: Sheep wool waste transformation into resources represents an important challenge. GIS analyses were carried out for investigating the available sheared sheep wool. Wool waste could be reused for new green building elements. Nowadays only few examples of wool waste recovery could be found in Italy. A new sheep wool valorization chain could be developed.